Milinda praśne emba adē hesarina Pāli brahadgranthada prakṣiptavenisida khaṇḍagaḷannu biṭṭu māḍida Kannaḍa anuvāda - Rajaratnam, G. P., 1909- (SAMP early 20th-century Indian books project ;, 1937)
Kannada translation of a Pali treatise on basic tenets of Buddhism, written in the form of dialog between Nāgasena and Milinda, i.e. Menandar, Indo-Greek king, fl. 150? B.C.